(untitled) (Bangladesh Journal of Medical Science, 2013)
Background: In recent time issues of career choices in medical student has been gaining mounting attention. Aim: The current study was planned with an aim to understand issues and dilemmas in career planning of medical students in Surat city, India Methods: This is a cross-sectional study comprising of personal interviews using a self -designed structured questionnaire among 400 simple randomly selected medical students, interns and junior residents of Surat Municipal Institute of Medical Education and Research covering issues associated with their career concerns and future life. Data analysis was done with help of Epi Info 7. The study sample comprised of students 46.5%, intern doctors 36%, junior resident doctors 17.5%. Results:Females were more content with either a graduate or a post graduate degree, whereas males were more inclined towards pursuing super specialty degrees (P<0.001). Majority 62% of the respondent stated that given another chance, they would again like to choose for medical studies only. The percentages of females interested in a non clinical career abroad as compared to clinical career in India were lower. Majority 89% of respondents agree that there is more struggle for the students who enter M.B.B.S. from a non medical background. Percentages of males in favor of increasing the postgraduate/super specialty seats far exceeded females (P<0.0001). The vast majority of the respondents wanted the specialty and super specialty seats to increase as they wanted an equal ratio of Undergraduate: Postgraduate seats (70%). Those who did not favor the increase in the seats perceived that the quality of treatment may actually worsen rather than improve if the number of seats increased (60%). Conclusion: Freshly graduating doctors do face a severe dilemma regarding their future career after graduation, which is a very perplexing situation for them and their parents, as there is absence of any career guidance cell; absence of the culture and avenues of campus placement; and there is human need to be materialistically comparable to their counterparts who are already in a job as an engineer. DOI: http://dx.doi.org/10.3329/bjms.v12i4.13336 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 385-391